Genomic identification and phenotypic evaluation of yield traits and bacterial wilt resistance in high oleic peanut breeding lines developed by marker assisted backcrossing - Yuanjin Fang; Hua Liu; Zhongxin Zhang; Feiyan Qi; Qingzheng Chen; Haidong Liu; Liyun Wan; Xiao Wang; Mengdi Tian; Dengyu Lv; Ziqi Sun; Wenzhao Dong; et al. (Euphytica, 2022)
The peanut rich in oleic acid in seed oil, also known as high oleic peanut, renders its products superior in human healthy diet, long shelf life and high oxidative stability in food and oil processing. High oleic peanut varieties in China are derived from a handful of high oleic donors with limited genetic background. Improvement of high oleic peanut cultivars by integrating key target traits is crucial for both food security and germplasm enhancement. Several superior high oleic peanut lines have been developed by marker assisted backcrossing in our breeding program. The objective of present study is to characterize bacterial wilt disease resistance and yield related traits in these novel peanut lines. The two-year disease nursery survival rates were used as an indicator for bacterial wilt resistance, and the diagnostic markers identified by QTL mapping were used for molecular verification. Genetic background of high oleic peanut lines was estimated by 40 K genotyping by target sequencing (GBTS) SNP panel. Preliminary and regional yield tests were performed for selected breeding lines in 2021. As a result, an elite high oleic peanut accession Yuhua183 was identified, inheriting the superior characteristics of its recurrent parent such as resistance to bacterial wilt, high shelling percentage and early maturity. The development of Yuhua183 broadened the genetic background of high oleic peanut germplasm, providing valuable genetic resources for peanut breeding and further utilization.